2005
DOI: 10.1098/rspb.2005.3152
|View full text |Cite
|
Sign up to set email alerts
|

Costly but worthless gifts facilitate courtship

Abstract: What are the characteristics of a good courtship gift? We address this question by modelling courtship as a sequential game. This is structured as follows: the male offers a gift to a female; after observing the gift, the female decides whether or not to accept it; she then chooses whether or not to mate with the male. In one version of the game, based on human courtship, the female is uncertain about whether the male intends to stay or desert after mating. In a second version, there is no paternal care but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Several scholars have argued that people can use gifts to signal their willingness to cooperate in future relationships (see Camerer 1988;Carmichael and MacLeod 1997;Bolle 2001;and Sozou and Seymour 2005). According to these models, gifts should be costly to the donor and have little value for the recipient.…”
mentioning
confidence: 99%
“…Several scholars have argued that people can use gifts to signal their willingness to cooperate in future relationships (see Camerer 1988;Carmichael and MacLeod 1997;Bolle 2001;and Sozou and Seymour 2005). According to these models, gifts should be costly to the donor and have little value for the recipient.…”
mentioning
confidence: 99%
“…Game theoretic analyses have shown that a particular kind of gift may serve as an effective commitment signal (Bolle, 2001;Camerer, 1988;Sozou & Seymour, 2005). The gift must not be too valuable to the recipient, lest the gift-giver become vulnerable to exploitation (e.g., by "gold diggers").…”
Section: Gift Givingmentioning
confidence: 99%
“…However, historically gifts were also used to signal intent between two parties attempting to form a transaction [48,49] and thus served as building stones of relationships by strengthening trust [50][51][52][53][54][55][56]. This leads to an important question: What is trust?…”
Section: Open Accessmentioning
confidence: 99%